The Principle of Legality in Criminal Act of Terrorism - Hariman Satria (Jurnal Cita Hukum, 2017)
The trial of Imam Samudera cs uses Perppu No 1 2002 on Combating Criminal Acts ofTerrorism. This regulation was made after Bali bombing 1. So the criminal provisions weremade retroactively. Similarly, in cases of serious human rights violations in East Timor, theperpetrators use retroactive laws. Enforcement of the criminal provisions retroactively alsomade by the ad hoc international criminal court through Nurenberg Trial and Tokyo Trial in1945. Enforcement of the criminal provisions aimed at fulfilling the principle of justice, thatthe convict by violating the principle of legality is not fair but not punishing guilty of seriouscrimes which did not fare much better. Strictly speaking, the principle of legality can crisis. DOI: 10.15408/jch.v5i2.4959